First line direct access for transarterial embolization of a dural arteriovenous fistula: Case report and literature review. (February 2018) - Doolan, Brent J.; Paldor, Iddo; Mitchell, Peter J.; Morokoff, Andrew P.
Highlights: Traditional transarterial embolization of an unusual DAVF could cause blindness. Direct transcranial access with catheterization provided successful embolization. A hybrid approach is proposed for DAVF too high risk for neurological deficit. Abstract: Intracranial dural arteriovenous fistulae (DAVF) are complex vascular malformations consisting of a pathological shunt located between meningeal arteries and drainage to dural venous sinuses and/or cerebral veins. We report an unusual anatomical variation, resulting in a DAVF forming between the superior sagittal sinus and an anomalous origin of the middle meningeal artery (MMA) arising from the left ophthalmic artery. We present an atypical case requiring mini-craniotomy for catheter access, as well as cannulation of extracranial arterial supply prior to embolization of a Cognard type IIa+b fistula. Due to structural variation, transarterial endovascular embolization was deemed too high risk owing to risk of permanent blindness. We present a technical note and literature review on the first documented case of combined endovascular and surgical intervention as first line treatment for embolization of an anomalous middle meningeal artery related fistula. Our approach provided adequate obliteration of the DAVF and may be an alternative way to treat DAVF, when traditional transarterial or transvenous approaches are deemed high risk for neurological deficit.